2018
DOI: 10.1088/1361-6463/aac818
|View full text |Cite
|
Sign up to set email alerts
|

Multi-modal millimeter-wave sensors for plastic polymer material characterization

Abstract: This paper presents, for the first time, a multimodal sensor for characterizing relative permittivity of plastic polymers by integrating in a single sensor (1) frequency-reconfigurable resonance technique at 98 and 100 GHz, and (2) 80-100-GHz broadband modified transmission-line technique. The sensor is designed based on a custom-made WR-10 waveguide featuring dual rectangular Complementary Split-Ring Resonators (CSRRs). By loading the CSRRs with a Material-Under-Test (MUT), the reflected and transmitted elect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 32 publications
1
5
0
Order By: Relevance
“…While the relative permittivity and loss tangent of SU-8 2000 were 3.22 and 0.025, respectively. Of note, this result of SU-8 2000 was strongly comparable to those previous published in [4].…”
Section: A Sensor Optimization and Materials Characterizationsupporting
confidence: 91%
See 2 more Smart Citations
“…While the relative permittivity and loss tangent of SU-8 2000 were 3.22 and 0.025, respectively. Of note, this result of SU-8 2000 was strongly comparable to those previous published in [4].…”
Section: A Sensor Optimization and Materials Characterizationsupporting
confidence: 91%
“…The short-circuited termination is inserted to one port on the sensor that the distance between this termination and the CSRR is kept at g/4. regarding the tailor-made WR10 waveguide fabrication can be found in [3]- [4]. Complete assembly of the sensor is shown in Fig.…”
Section: Fabrication and Integration Structurementioning
confidence: 99%
See 1 more Smart Citation
“…e local mobility and nature of the polymer-polymer interactions can be investigated through dielectric relaxation [31]. Recent studies have revealed that there are several methods for [32][33][34][35][36]. In particular, impedance measurements at various frequencies are found to be an accurate method to study the molecular motion of dielectric materials at different temperatures [29,36].…”
Section: Dielectric and Electric Modulus Studymentioning
confidence: 99%
“…With microwave measurement techniques, there are several methods to indicate liquid ingredients from liquid-mixture solutions, e.g., resonance frequency [18], [30]- [32], transmission level [17], [32]- [33], phase and quality factor (Q-factor) [23]. Various liquid-mixture sensors based on microwave technologies have been extensively investigated, such as split-ring resonator [34]- [36], complementary split-ring resonator (CSRR) structures [17], [31]- [32], [37]- [38], interdigital structures [8], substrate integrated-waveguide (SIW) structures [18], waveguide structures [30] and mushroom-like structures [23]. These techniques offer a good measurement accuracy [17]- [18], [31], with, generally, nondestructive measurement and short assay time.…”
Section: Introductionmentioning
confidence: 99%